Ensino das relações métricas do triângulo retângulo com robótica educacional - Santos, Marden Eufrasio dos (2016)
The Rectangle Triangle Metrics Relations is an important content of geometry in elementary school and the basis for the study of trigonometry in high school, with great potential for application in solving mathematical problems. Given the difficulties with the learning of this content, we developed a teaching plan, based on Constructive alignment, integrating Educational Robotics in teaching this subject of mathematics, considering the development of two skills: (i) visualization and application of the properties of geometric figures; and (ii) development of deductive reasoning in building solutions to the problems proposed. Integration of Educational Robotics in Mathematics Teaching, as proposed in this study, was assessed by a case study of 30 students of the 9th grade of elementary school of a public school named Deyse Lammel Hendges, in the county of Presidente Figueiredo (AMAZONAS). The case study results showed an improvement in students’ learning, and the most significant rates were achieved in the development of visualization skill and application of geometric properties. Regarding the second skill - development of deductive reasoning to solve problems - the results were more modest, as the development of calculations required knowledge of arithmetic, whose mastery by students was limited, even in the case of students in last year of elementary school. As a product of this work, we organized an Educational Robotics Application Notebook for Mathematics Teaching focusing on the Rectangle Triangle Metrics Relations. The notebook is organized into three parts: in Part one, we find a guideline for development of mathematical problems with the use of Educational Robotics. In Part two, indications on Educational Robotics kits and other resources to help the teachers. In Part three, a guideline for the implementation of the educational planning developed in the format of a course.